Myth and Ideology in Smartphone Advertisement - Agustia, Km. Tri Sutrisna; Beratha, Ni Luh Sutjiati; Pastika, I Wayan; Sukarini, Ni Wayan (e-Journal of Linguistics; Vol 20 No 1 (2026): ejl-JanuaryDO - 10.24843/e-jl.2026.v20.i01.p06, 2025)
In the digital era, smartphone advertising extends beyond the promotion of technical features and increasingly functions as a medium for constructing cultural meanings, myths, and ideologies. This study examines YouTube advertisements for the Samsung Galaxy A34 using Roland Barthes’ semiotic framework, which includes the levels of denotation, connotation, myth, and ideology. Through qualitative analysis, the research identifies how visual narratives and technological representations in the commercials generate symbolic associations with empowerment, mobility, multicultural harmony, and futurism. These connotative meanings evolve into broader cultural myths that portray technology as a liberating force, a unifying agent, and a marker of social progress. At the ideological level, the advertisements naturalize values of modernity, consumerism, technological determinism, and hyper-individualism. Additionally, the study highlights YouTube’s algorithmic and multimodal features, which amplify the reach and ideological influence of such advertisements by enabling targeted dissemination and interactive user engagement. The findings demonstrate that YouTube smartphone commercials function not only as marketing tools but also as cultural texts that shape societal perceptions of technology, identity, and modern life.